2020
DOI: 10.1111/are.14990
|View full text |Cite
|
Sign up to set email alerts
|

Characterization ofStreptococcus iniaeghost vaccine and its immunization in Nile tilapia (Oreochromis niloticus)

Abstract: Streptococcus iniae (S. iniae) is a Gram‐positive bacterium associated with disease in several commercial species and other animals including humans. This zoonotic pathogen has led to high worldwide morbidity and mortality and huge economic losses in aquaculture. Here a S. iniae ghost (SIG) vaccine was successfully generated with a chemical method, and its immunogenicity and protective efficacy were examined in this study. The results showed that the titres of immunoglobulin M (IgM) in serum were significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Although inactivated vaccines often show less efficacy against viral or intracellular bacterial infection [ 11 ], the bacterin provides sufficient protection against several bacterial infections, such as vibriosis [ 12 , 13 ], furunculosis [ 14 ], and streptococcosis [ 15 ]. Inactivated vaccines against S. iniae in fish have been widely studied in several species, such as Nile tilapia ( Oreochromis niloticus ) [ 15 , 16 , 17 ], grouper ( Epinephelus coioides ) [ 18 ], zebrafish ( Danio rerio ) [ 19 ], rainbow trout ( Oncorhynchus mykiss ) [ 20 , 21 , 22 ], and Asian seabass [ 23 , 24 ]. Studies in Asian seabass showed the efficacy of inactivated vaccines against experimental challenge at 60 and 79 days post-vaccination and the increasing IgM response to vaccination [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although inactivated vaccines often show less efficacy against viral or intracellular bacterial infection [ 11 ], the bacterin provides sufficient protection against several bacterial infections, such as vibriosis [ 12 , 13 ], furunculosis [ 14 ], and streptococcosis [ 15 ]. Inactivated vaccines against S. iniae in fish have been widely studied in several species, such as Nile tilapia ( Oreochromis niloticus ) [ 15 , 16 , 17 ], grouper ( Epinephelus coioides ) [ 18 ], zebrafish ( Danio rerio ) [ 19 ], rainbow trout ( Oncorhynchus mykiss ) [ 20 , 21 , 22 ], and Asian seabass [ 23 , 24 ]. Studies in Asian seabass showed the efficacy of inactivated vaccines against experimental challenge at 60 and 79 days post-vaccination and the increasing IgM response to vaccination [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%